Soft-switching of IGCTs in three-level voltage source inverter - Szular, Zbigniew; Mazgaj, Witold (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This paper presents a soft-switching system in three-level voltage source inverters based on Integrated Gate-Commutated Thyristors. The proposed soft-switching system refers to inverter thyristors connected to the voltage source terminals. The operation principles of the inverter equipped with the proposed soft-switching solution are discussed in detail herein. The main thyristors are controlled in the same manner as those in an inverter operating with a hard-switching technique. The correctness of the IGCT model used in the calculations is verified by comparing numerically obtained voltage and current with waveforms recorded at the laboratory stand. Numerical analysis is performed for the voltage source inverter of the rated power of 10 MW (2×2.5 kV, 3.0 kA). Examples of voltage and current waveforms for a single switching of one of the main thyristors and selected waveforms for two periods of the inverter output voltage are presented. The switching losses of the three-level voltage source inverter with the described soft-switching system are compared with those in an inverter with the hard-switching technique. The proposed soft-switching solution allows for increasing inverter efficiency.